Characterization of S3Pvac Anti-Cysticercosis Vaccine Components: Implications for the Development of an Anti-Cestodiasis Vaccine - Rassy, Dunia; Bobes, Raul J.; Rosas, Gabriela; Anaya, Victor H.; Brehm, Klaus; Hernandez, Beatriz; Cervantes, Jacquelynne; Pedraza, Saul; Morales, Julio; Villalobos, Nelly; de Aluja, Aline S.; Laclette, Juan P.; et al. (Public Library Science, 2010)
Background: Cysticercosis and hydatidosis seriously affect human health and are responsible for considerable economic loss in animal husbandry in non-developed and developed countries. S3Pvac and EG95 are the only field trial-tested vaccine candidates against cysticercosis and hydatidosis, respectively. S3Pvac is composed of three peptides (KETc1, GK1 and KETc12), originally identified in a Taenia crassiceps cDNA library. S3Pvac synthetically and recombinantly expressed is effective against experimentally and naturally acquired cysticercosis.Methodology/ Principal Findings: In this study, the homologous sequences of two of the S3Pvac peptides, GK1 and KETc1, were identified and further characterized in Taenia crassiceps WFU, Taenia solium, Taenia saginata, Echinococcus granulosus and Echinococcus multilocularis. Comparisons of the nucleotide and amino acid sequences coding for KETc1 and GK1 revealed significant homologies in these species. The predicted secondary structure of GK1 is almost identical between the species, while some differences were observed in the C terminal region of KETc1 according to 3D modeling. A KETc1 variant with a deletion of three C-terminal amino acids protected to the same extent against experimental murine cysticercosis as the entire peptide. on the contrary, immunization with the truncated GK1 failed to induce protection. Immunolocalization studies revealed the non stage-specificity of the two S3Pvac epitopes and their persistence in the larval tegument of all species and in Taenia adult tapeworms.Conclusions/ Significance: These results indicate that GK1 and KETc1 may be considered candidates to be included in the formulation of a multivalent and multistage vaccine against these cestodiases because of their enhancing effects on other available vaccine candidates.